Association of Genetics traits with obesity in men: A review on the current knowledge in Iran - Akhoundi Khoranaghi, Arezoo; Nematollahi, Shahrzad; AliAkbary, Fereshteh; Shariatpanahi, Samira (Archives of Men's Health, 2020)
Today, obesity is one of the leading causes of death. It also causes other diseases such as diabetes, cardiovascular disease, and various types of cancer. Obesity is a multifactorial disease caused by factors such as genetics and lifestyle. However, scientists imagine that about 40-70% of the disease originates from genetics. In this review, we examined the role of different genes in obesity by examining 30 articles published on the role of genetics in the obesity of Iranian men, according to their BMI, comorbidities and family history. We concluded that most of the research has been done on the FTO, Hind III and S447 genes. We also showed an apparent relationship between these genes and obesity. Finally, according to studies, FTO can be considered as the most important and strongest contributor to obesity.